Studies in law, politics, and society. Volume 82 - Sarat, Austin (Bingley, U.K. : Emerald Publishing Limited, 2020)
This volume of Studies in Law, Politics and Society brings together an international and interdisciplinary array of scholars to explore issues on the cutting edge of socio-legal research. They consider the complex connections of liberal democracy, human rights, governance in and through courts, the challenges terrorism poses to criminal law, and the problematics of global governance. Taken together, the chapters in this volume point to exciting new directions for legal scholars.
Chapter 1. Overcoming liberal democracy: 'threat governmentality' and the empowerment of intelligence in the UK Investigatory Powers Act / Christos Boukalas -- Chapter 2. Judicial reform and legal opportunity structure: the emergence of strategic litigation against femicide in Mexico / Vero'nica Michel -- Chapter 3. Avoiding international human rights law in the pursuit of peace / Chris Kendall -- Chapter 4. Criminalization and the rights bearing subject: considering the lived experiences of governance in the juvenile court / Elizabeth Brown and Amy Smith -- Chapter 5. Claiming food sovereignty: legal mobilization in an era of global governance / Matthew C. Canfield -- Chapter 6. How entrapment still matters: partial successes of entrapment claims in terrorism prosecutions / Jesse J. Norris.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: International law; Human rights; Law -- International; International law